Examination of job and life satisfaction of academicians - Nehir, Sevgi; Durgu, Nihan; Ozcan, Fatih; Oryal Taskin, Emin (Annals of Medical Research, 2021)
Aim: The aim of the study is to examine the job and life satisfaction levels of academicians and determine the relationship between job and life satisfaction.Materials and Methods: The sample of this cross-sectional descriptive study consisted of 338 academic staff (health, social) working at Manisa Celal Bayar University between November 2018 and June 2019. Data were collected via Information Form, Life Satisfaction Scale (LSS) and Job Satisfaction Scale (JSC). Data were analyzed using number, percentage, Kruskal Wallis H test, Student t test, One way ANOVA test, Spearman Correlation Analysis and Linear regression analysis. Results: According to the results of the correlation analysis, there was a high positive correlation (rs: 0.608) between the total score of LSS and JSC of academicians. According to regression analysis, it was seen that disease condition, mobbing and physical conditions satisfaction variables explained 15% of LSS score variance. Also, it was seen that disease condition, working year in the institution, managerial duties in the institution, mobbing and physical conditions satisfaction variables explained 36% of JSS score variance. Conclusion: Job and life satisfaction of academicians positively affects each other. Another important result, disease condition, mobbing and satisfaction with physical conditions, is very important for both the job satisfaction and life satisfaction of individuals.